Pengembangan media pembelajaran berbasis android dengan Lectora Inspire pada mata kuliah Kimia Anorganik II - Wiwit Alwi; Hermansyah Amir; Emilia Febrianti (ALOTROP, 2022)
This study aims to determine the level of feasibility, student responses, and improvement of student learning outcomes after using teaching materials developed using Lectora Inspire on Inorganic Chemistry II material. The development of teaching materials uses a 4D development model. The research subject was students of the Chemistry Education Study Program of the University of Bengkulu. The instruments in this study were undergraduate student questionnaires, validation sheets, pretest, and posttest sheets. It was found that (1) the media developed using Lectora Inspire were declared very feasible by media and material experts with percentages of 89.8% and 90.5%, (2) students' responses to the teaching materials used developed using Lectora Inspire is in the excellent category with an average percentage of 88.8%, (3) an increase in learning outcomes as measured by the average N-gain score 0.64 on the moderate criteria. The media developed using Lectora Inspire can be used as teaching materials to improve students' understanding of Inorganic Chemistry II material.   Keywords: media, learning outcomes, inorganic chemistry, chemistry bonding